Analysis of Factors Affecting Carbon Emissions on 10 G-20 Countries - Gilberth Bully; Lavlimatria Esya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This research aims to analyze the factors that influence Carbon Emissions in 10 countries that aremembers of the G20. The dependent variable used is Carbon Emissions (CO2), while theindependent variables are: Carbon Pricing, Fossil Fuel Subsidies, Manufacturing Exports andResearch and Development Expenditure. This research uses annual data obtained from the WorldBank, Our World in Data, and Fossil Fuels Tracker for the 2010-2021 period. The analyticalmethod used in this research is panel data regression. The model chosen in the panel dataregression is the Fixed Effect Model (FEM) with the results showing that the variables CarbonPricing, Fossil Fuel Subsidies, Manufacturing Exports and R&D Expenditure have a significantinfluence on Carbon Emissions (CO2).